Temperature dependences of the magmatic rocks electrical properties in the region of Akademik Vernadsky - Shepel, S. I.; Burtny, P. A.; Karnauchova, E. E. (Ukrainian Antarctic Journal, 2004)
The character of the temperature dependences of the specific electrical resistance, relative dielectric constant, activation energy of the current carriers of crystal rocks collected in the area of the Antarctic station Akademik Vernadsky was investigated. Measurements of electrical parameters were carried out on the different frequencies of the electromagnetic field in the temperature field up to 900° C. Some intervals with different temperature gradients of electrical parameters are revealed, which are determined by a type of rocks and frequency of the electromagnetic field. It was revealed that the reduction of the grain sizes of diorites results in decreases of the activation energy, electroresistance and raises of the dielectric constant.